Night Flight to Dungavel : Rudolf Hess, Winston Churchill, and the Real Turning Point of WWII - Padfield, Peter (Book collections on Project MUSE., 2013)
Until now there has been no satisfactory answer to the question of why, in May of 1941, Hitler's deputy Rudolf Hess flew a German fighter plane across the channel to Scotland, crashing at night in a muddy field near Dungavel House. Though Hess had been one of Hitler's closest confidantes he was immediately denounced as a traitor in Berlin. Imprisoned in England, he was questioned by British MI6 and Churchill himself. The documents he had brought with him were confiscated and have not been made public to this day. Hess was tried at Nuremberg at the war's end and imprisoned at Spandau in Berlin, one of only seven former Nazis held there. The other six were all released, but Hess lingered there alone until his death in 1987, possibly by suicide, possibly not. The official report on Hess has always been that he acted alone, but many historians question this conclusion. In Night Flight to Dungavel, award winning historian Peter Padfield presents striking new evidence that spurs a wholesale reappraisal of the mystery: what actually happened, what role was played by Churchill and British intelligence, and what has been this episode's significance as a real turning point of the war. Expertly woven into a compelling narrative that touches on Nazi sympathizers among the British aristocracy, possible British foreknowledge of the "final solution", and the mysterious circumstances of Hess's death in Spandau prison, Night Flight to Dungavel is among the most important and gripping stories of World War II.